Pembentukan Lingkungan Bahasa Arab Untuk Mengembangkan Keterampilan Berbicara - Irhamudin Abdullah; Novita Rahmi; Walfajri Walfajri (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2020)
This study aims to determine that the formation of the language environment is a major factor in the success of learning foreign speaking skills especially Arabic. The method used is the library research method (library research), data collection is done by examining and exploiting several journal articles, books, and other sources of information deemed relevant to the study. The formation of a language environment is one of the dominant factors supporting the success of learning Arabic speaking skills. It can be seen that speaking skills are very important language skills. Without an optimal language environment, it is difficult to master it. The results of this study are that the formation of the language environment must be the responsibility of the school manager and all boarding officials by involving all students. Thus, all parties will feel the language environment and support wholeheartedly towards all programs related to the language environment. The formation of the language environment can be done through various linguistic activities, including: developing vocabulary (mufrodat), displaying Arabic vocabulary (posters) in language environment facilities, Arabic language practices in daily communication, Arabic speech and drama practices.